Utility of microfluidic devices to study the platelet–endothelium interface. (4th July 2017) - Zilberman-Rudenko, Jevgenia; Sylman, Joanna L.; Garland, Kathleen S.; Puy, Cristina; Wong, Andrew D.; Searson, Peter C.; McCarty, Owen J. T.
Abstract: The integration of biomaterials and understanding of vascular biology has led to the development of perfusable endothelialized flow models, which have been used as valuable tools to study the platelet–endothelium interface under shear. In these models, the parameters of geometry, compliance, biorheology, and cellular complexity are varied to recapitulate the physical biology of platelet recruitment and activation under physiologically relevant conditions of blood flow. In this review, we summarize the mechanistic insights learned from perfusable microvessel models and discuss the potential utility as well as challenges of endothelialized microfluidic devices to study platelet function in the bloodstream in vitro .